APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN SEJARAH DI ABAD 21 - Ahmad Ruslan; Sugiono Sugiono; Andi Andi; Oky Firlana; Gery Erlangga (Universitas Muria Kudus, 2023)
The purpose of this study is to examine related to sophisticated, imaginative and inventive digital-based learning media through recorded learning involving the Canva application in history learning so that it can create an innovative atmosphere in the learning process.The research method used is descriptive qualitative with data collection techniques using documentation techniques and literature research analysis techniques to arrive at the stage of drawing a conclusion.The results of the study show that the use of the Canva application in learning history is an interesting and creative learning medium in accordance with the development of 21st century schools, especially in all parts of the use of innovation in everyday life. Thus, the final conclusion in writing this article explains that the Canva application is very easy and practical to access in learning activities. The application of the Canva application in history learning is the right solution to assist educators in creating computerized learning media in the 21st century so that the delivery of learning materials can be more easily accepted by students.